Portraying The “Other”: Scrutinizing The Lexical Markers in American and Iranian Editorial Articles on Us-Iran Tensions - Marquez, Junar; Chavez, Anna Rose; Gochuico, Maria Theresa (International Journal of Language and Literary Studies, 2026)
Addressing the historical and methodological gap observed in the reviewed related studies, this paper, as guided by Fairclough’s Three-Dimensional Model and Moscovici’s Social Representation Theory, has employed a Descriptive Qualitative Research design to initiate a Critical Discourse Analysis in scrutinizing the frequent lexical markers used in American and Iranian editorial articles and how these markers construct the social representations of the United States (US) and Iran within their respective cultural viewpoints. The articles included in this study were extracted from the New York Post and Mehr News Agency and were published from February 28 to April 7, 2026. The analysis revealed that the American and Iranian articles frequently used the lexical marker “regime” to portray each other negatively. Particularly, the American articles denotatively utilized this marker to illegitimize Iran as a sovereign state due to its uncontrollability and unpredictability. Meanwhile, such a marker was connotatively used in the Iranian articles to capture the perceived repressive attitude of the US towards Iran. Therefore, it is concluded that both sets of editorial articles have “othered” their respective countries in the positive polarity of the ongoing conflict. Furthermore, the social representations associated with the US flip the traditional perception of Iran as an authoritarian state. Conversely, this portrays the US as an entity that threatens global stability. With this, it is recommended for future studies to consult other media platforms as a corpus to confirm the consistency of these social representations.